1984
DOI: 10.1002/art.1780271210
|View full text |Cite
|
Sign up to set email alerts
|

The production of collagenase by adherent mononuclear cells cultured from human peripheral blood

Abstract: Mononuclear cells were isolated from human peripheral blood by Ficoll-Hypaque centrifugation, and the cells adherent to plastic substrata were cultured in serum-free media supplemented with lactalbumin hydrolysate. These cell cultures, which consisted predominantly of monocyte-macrophages as judged by nonspecific esterase staining, accumulated collagenase in the medium. This collagenase resembled other vertebrate collagenases in that it cleaved native triple-helical type I collagen at a locus Y4-length away fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
1

Year Published

1986
1986
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 28 publications
0
11
1
Order By: Relevance
“…49,50 Moreover, CCR2 was expressed by intratumoral F4/80-positive macrophages, which can secrete various angiogenc factors and MMP, including bFGF and MMP9. [42][43][44]51 CCR2 deficiency resulted in the reduction in bFGF and MMP9 gene expression marginally but not significantly, with a concomitant apparent reduction in macrophage infiltration. Thus, in this model, CCR2-mediated signals induced the accumulation of macrophages, which can contribute to neovascularization by secreting these factors, in concert with MMP2 expressed mainly by HSCs.…”
Section: Discussionmentioning
confidence: 99%
“…49,50 Moreover, CCR2 was expressed by intratumoral F4/80-positive macrophages, which can secrete various angiogenc factors and MMP, including bFGF and MMP9. [42][43][44]51 CCR2 deficiency resulted in the reduction in bFGF and MMP9 gene expression marginally but not significantly, with a concomitant apparent reduction in macrophage infiltration. Thus, in this model, CCR2-mediated signals induced the accumulation of macrophages, which can contribute to neovascularization by secreting these factors, in concert with MMP2 expressed mainly by HSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Louie et al (38) demonstrated interstitial collagenase activity in the media of peripheral blood monocyte cultures after 3 d of in vitro differentiation that could be upregulated by the addition of phorbol myristic acetate or concanavalin A. In contrast, Gadek et al (39) reported that collagenase activity in cultures of human alveolar macrophages was expressed in a constitutive manner.…”
Section: Discussionmentioning
confidence: 99%
“…Among their activities potentially involved in such remodeling is production of collagenase, the enzyme that initiates the cleavage of native collagen (36) and of inhibitory molecules that specifically block this enzyme's catalytic function. A number of studies have demonstrated the release of collagenase activity from animal mononuclear phagocytes (37,38) and recently these observations have been extended to human peripheral blood monocytes (39) and alveolar macrophages (7) in culture. The production of both collagenase and collagenase inhibitor proteins by alveolar macrophages (7) and by TPA-differentiated U937 cells provide conclusive evidence that human mononuclear phagocytes can directly modulate the turnover of collagen.…”
Section: Discussionmentioning
confidence: 99%